2011
DOI: 10.1029/2011wr010547
|View full text |Cite
|
Sign up to set email alerts
|

Determining longitudinal dispersion coefficients for submerged vegetated flow

Abstract: [1] Prediction of the physical transport and mixing of pollutants or other soluble material is crucial for effective river management. Although well established methods exist which describe mixing processes in open channel flow, the presence of vegetation has a significant impact on mixing and few existing techniques account for this. To date, existing models which predict longitudinal dispersion coefficients in vegetated open channel flow have been derived and verified based on experiments conducted in simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 38 publications
2
50
0
Order By: Relevance
“…The presence of in-stream vegetation thereby reduces the exchange rates, increasing the release timescale of solute retention (Hendricks and White 1991;Harvey and Bencala 1993;Brunke and Gonser 1997;Cardenas et al 2004). A number of studies have attempted to quantify the effect of submerged and emergent vegetation on the dispersion of solutes (Nepf 1999;Nepf et al 2007;Shucksmith et al 2011) and the storage effects associated with microbial biofilms (Battin et al 2003;Bottacin-Busolin et al 2009). …”
Section: The Effect Of Vegetationmentioning
confidence: 99%
“…The presence of in-stream vegetation thereby reduces the exchange rates, increasing the release timescale of solute retention (Hendricks and White 1991;Harvey and Bencala 1993;Brunke and Gonser 1997;Cardenas et al 2004). A number of studies have attempted to quantify the effect of submerged and emergent vegetation on the dispersion of solutes (Nepf 1999;Nepf et al 2007;Shucksmith et al 2011) and the storage effects associated with microbial biofilms (Battin et al 2003;Bottacin-Busolin et al 2009). …”
Section: The Effect Of Vegetationmentioning
confidence: 99%
“…Liu et al [22] studied longitudinal dispersion in flow along the floating vegetation patch. They also indicated that a large number of studies on the longitudinal dispersion in open-channel flows with submerged and emergent vegetation have been presented [16,[23][24][25]. However, there is an insufficient number of studies on the effects of floating vegetation patches in the literature [22].…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic model is widely used to simulate the flow circulation, temperature dynamics, contaminant transport and advanced eutrophication processes (Nepf, 2012). It has also been applied in the simulation and decision support analysis of surface water such as lakes, reservoirs, bays, wetlands and estuaries (Shucksmith et al, 2011;Wu et al, 2o14;Wang et al, 2015). By comparison, ecological models can simulate a variety of ecological processes, dynamics across multi-species at different trophic levels, and can be used to establish a quantitative linkage between external nutrient loading, internal water quality conditions and holistic ecosystem response.…”
Section: Introductionmentioning
confidence: 99%